Variability of trace-elements and δ18O in drip water from Gruta del Rey Marcos, Guatemala; seasonal and environmental effects, and its implications for paleoclimate reconstructions - Bernal, J. P.; Revolorio, F.; Cu-Xi, M.; Lases-Hernández, F.; Piacsek, P.; Lachniet, Matthew S.; Beddows, Patrica A.; Lucia, G.; López-Aguiar, K.; Capella-Vizcaíno, S.; López-Martínez, R.; Vásquez, O. J. (Frontiers in Earth Science, 2023)
Guatemala is located at the core of one of the largest warming pools in the planet, the Western Hemisphere Warm Pool, an important source of tropical moisture to middle and high latitudes and, thus, a key area for paleoclimatic studies. This, along the karst pervasiveness in the area provides the opportunity to obtain high-resolution records of past hydroclimatic conditions using stalagmites. Despite this, the atmospheric and geochemical processes that might affect the variability of geochemical proxies in stalagmites are yet to be constrained, as no cave-monitoring in the area has been carried out previously. Here, we present a 2.5-year cave-monitoring study from Gruta del Rey Marcos, Guatemala, which allows to understand the effect of external atmospheric and environmental conditions upon the variability of δ18O, Mg/Ca, Sr/Ca, and Ba/Ca in drip water. By incorporating cave ventilation dynamics, isotopic information of local rainfall and cave-river water, we are able to understand the most relevant processes that affect the variability of the geochemical proxies in drip water, hence stalagmites. Our results suggest that two-isotopically distinct rainfall regimes, as well as tropical cyclones affecting the area contribute to the composition of the drip-water, hence the resulting stalagmites, with low δ18O ( -6‰ VSMOW) values indicative of strong convective activity, whilst high δ18O values (-4.5 and -5 ‰ VSMOW), are indicative of poor convection and proportionally more significant winter-frontal rainfall. We also demonstrate that the trace-element composition of drip water is largely modulated by PCP, and thus, the variability in underlying stalagmites can be interpreted to reflect changes in karst humidity, with low E/Ca ratios (E = Mg, Sr, Ba), indicative of a wet epikarst and high E/Ca ratios indicative of a dry epikarst. Our results provide essential information for the interpretation of the δ18O and trace element variability in stalagmites, which can result in robust paleoclimatic reconstructions from Gruta del Rey Marcos and elsewhere in central America and southern Mexico